Situating Women Gender Politics and Circumstance in Fiji - George, Nicole (ANU Press, 2012)
Since the time of decolonisation in Fiji, women's organisations have navigated a complex political terrain. While they have stayed true to the aim of advancing women's status, their work has been buffeted by national political upheavals and changing global and regional directions in development policy-making. This book documents how women activists have understood and responded to these challenges. It is the first book to write women into Fiji's postcolonial history, providing a detailed historical account of that country's gender politics across four tumultuous decades. It is also the first to examine the 'situated' nature of gender advocacy in the Pacific Islands more broadly. It does this by analysing trends in activity, from women's radical and provocative activism of the 1960s to a more self-evaluative and reflexive mood of engagement in later decades, showing how interplaying global and local factors can shape women's understandings of gender justice and their pursuit of that goal.